STRATEGI BAURAN PROMOSI DAN ANALISA SWOT PADA ERA NEW NORMAL (STUDI PADA SEKOLAH SWASTA DYNATA BALI) - Nitaleari, Ni Wayan; Gorda, A.A.N. Eddy Supriyadinata (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p07, 2022)
Becoming a favorite private school in providing educational services is the dream of every education service provider. The COVID-19 pandemic has caused a reduction in the interest of new students to attend private schools, making it difficult for new education service providers to develop and provide the best education services. This study aims to determine the promotion mix strategy and SWOT analysis of private elementary schools in Bali in the New Normal era. This research is a qualitative research sourced from interviews. The object of this research is Dynata Elementary School. The result of this research is that the Dynata school can formulate a ST strategy that is using strength to overcome threats and based on the promotion mix it can focus on the dimensions of sales promotion and personal selling. This research can be useful for education service providers who are relatively new to be able to compete in the New Normal Era.